2020
DOI: 10.1213/ane.0000000000004729
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Intraoperative Intravenous S-Ketamine in Opioid-Naïve Patients After Major Lumbar Fusion Surgery Is Temporary and Not Dose-Dependent: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Background: Severe pain often accompanies major spine surgery. Opioids are the cornerstone of postoperative pain management but their use can be limited by numerous side effects. Several studies claim that adjuvant treatment with intravenous (IV) ketamine reduces opioid consumption and pain after back surgery. However, the exact role of ketamine for this indication is yet to be elucidated. We compared 2 different doses of S-ketamine with placebo on postoperative analgesic consumption, pain, and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 30 publications
3
78
1
Order By: Relevance
“…This oxycodone:S-ketamine ratio is also well tolerated. As previous studies have mainly focused on intraoperative administration, even showing no analgesic effect of intraoperative S-ketamine in opioid-naïve patients [ 38 ], this finding adds new data to the feasibility of adjunct S-ketamine with oxycodone for postoperative pain management after major lumbar spinal fusion surgery.…”
Section: Discussionmentioning
confidence: 63%
“…This oxycodone:S-ketamine ratio is also well tolerated. As previous studies have mainly focused on intraoperative administration, even showing no analgesic effect of intraoperative S-ketamine in opioid-naïve patients [ 38 ], this finding adds new data to the feasibility of adjunct S-ketamine with oxycodone for postoperative pain management after major lumbar spinal fusion surgery.…”
Section: Discussionmentioning
confidence: 63%
“…For subgroup analyses, we identified 5 groups, which included 3 or more trials: nonsteroidal anti-inflammatory drugs (NSAIDs), 3 , 55 , 59 , 62 , 71 epidural analgesia, 2 , 7 , 21 , 32 , 60 ketamine infusion, 1 , 5 , 24 , 41 , 53 , 64 , 66 local infiltration analgesia, 6 , 22 , 44 , 61 and intrathecal (i.t.) morphine.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials reported on PONV. 1,5,41,53,64,66 The meta-analysis found no significant difference between groups, RR 0.99 (95% CI: 0.76–1.28) with low heterogeneity I 2 = 12% (Appendix 5, available at http://links.lww.com/PR9/A157). The quality of evidence (GRADE) was very low (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A very recent RCT on perioperative ketamine concluded that most of the 189 patients in the study complained of disturbed sleep on the night following surgery. However, there were no significant differences between the ketamine and placebo groups [ 57 ], neither were there significant differences between the groups regarding hallucinations or confusion, and no patients reported vivid dreams or nightmares.…”
Section: Perioperative Sleep Disturbancesmentioning
confidence: 99%